Effects of the Sports Level, Format of the Game and Task Condition on Heart Rate Responses, Technical and Tactical Performance of Youth Basketball Players - Clemente, Filipe Manuel (J Hum Kinet, 2017)
The aim of this study was to analyze the effect of different small-sided and conditioning games (SSCG) with different tactical contents on heart rate responses, technical performance and collective organization of youth basketball players of different performance levels. Twenty male basketball players from U14 (13.7 ± 0.8 years old; 4.2 ± 1.4 years of practice) and U16 (15.3 ± 1.1 years old; 6.4 ± 2.1 years of practice) participated in this research study. The two-way MANOVA revealed that the sports level (p = 0.009; [Image: see text] = 0.151), format (p = 0.001; [Image: see text] = 0.246) and task condition (p = 0.023; [Image: see text] = 0.104; small effect size) had significant main effects on heart rate responses. It was also found that the format (p = 0.001; [Image: see text] = 0.182) had significant main effects on technical performance. A smaller format significantly increased the heart rate, volume of play, efficiency index and collective density during attacking plays. The SSCG with attacking content statistically increased the heart rate, efficiency index and performance score. Therefore, this study revealed that different SSCGs with tactical content influenced the physiological responses of youth players.